Antagonistic Characteristics and Phytochemical Screening of Invasive Alien Species of Nepal Himalaya - Baral, Bikash (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The bioclimatic diversity of Nepal favors many alien species to become naturalized invading and dominating intact natural communities. The ability of these plants to tolerate severe harsh conditions and become invasive lights on the potentiality of their use in the pharmacology. In the present study, a bioassay directed phytochemical analysis of the five major invasive alien species of Nepal was carried out. The extracts of the alien species (Ageratina adenophora, Eichhornia crassipes, Lantana camara, Mikania micrantha and Parthenium hysterophorus) were prepared by hot and cold process using methanol and water as solvents. The antimicrobial (against 10 clinical bacteria and 9 phytopathogenic fungi) activity of different concentration (50, 100, 150, 200 mg/ml) of various plant extracts was studied. The qualitative phytochemical analysis depicted the presence of polyoses, saponins, polyphenols, reducing compounds, alkaloids, glycosides, quinones, flavonic glycosides and coumarins in the plants. The extracts were found to be more effective against the fungal pathogens that may be due to the presence of different bioactive compounds in the plants and their action towards the pathogens. This study improves our knowledge on the scope and use of the plants to control the different pests, to isolate the bioactive compounds and the further strategies on the effective management of these invasive species.Key words: antibacterial, antifugal, plant extracts, zone of inhibition